The black death the intimate story of a village, 1345-1350 - Hatcher, John (Phoenix, 2008)
The Black Death remains the greatest disaster to befall humanity, killing about half the world's population in the 14th century. John Hatcher recreates everyday medieval life in the parish of Walsham le Willows, Suffolk, from which an exceptional number of documents survive. This enables us to view events through the eyes of its residents.